2017
DOI: 10.1590/1806-9061-2016-0319
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Cecal Bacteria Counts of Broilers Fed Low Protein Diets With and Without a Combination of Probiotic and Prebiotic

Abstract: KeywordsBroiler, low protein diet, prebiotic, probiotic.Submitted: June/2016 Approved: November/2016 ABStRACt A total of 360 one-day-old Cobb 500 chicks were randomly distributed in a completely randomized design according to a 3×2 factorial arrangement, consisting of three levels of dietary crude protein (100, 90 and 85% of NRCrecommended levels) and a feed additive (with or without feed additive). A blend of a commercial probiotic and a prebiotic were used as feed additives. Each treatment had four repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In line with the obtained results, some authors indicated that carcass weight showed a positive linear trend with the probiotic level ( Azadegan Mehr et al., 2007 ; Pourakbari et al., 2016 ). In addition, previous reports showed that probiotic supplements reduce the percentage of abdominal fat ( Anjum et al., 2005 ; Azadegan Mehr et al., 2007 ; Ravangard et al., 2017 ). The detected increased percentage of liver weight in ducks fed with a low protein level (14% CP) may indicate the presence of fatty liver or the occurrence of inflammation as a result of an imbalance in energy-to-protein ratio in the diet and the consequent hormonal and metabolism imbalance ( Rozenboim et al., 2016 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In line with the obtained results, some authors indicated that carcass weight showed a positive linear trend with the probiotic level ( Azadegan Mehr et al., 2007 ; Pourakbari et al., 2016 ). In addition, previous reports showed that probiotic supplements reduce the percentage of abdominal fat ( Anjum et al., 2005 ; Azadegan Mehr et al., 2007 ; Ravangard et al., 2017 ). The detected increased percentage of liver weight in ducks fed with a low protein level (14% CP) may indicate the presence of fatty liver or the occurrence of inflammation as a result of an imbalance in energy-to-protein ratio in the diet and the consequent hormonal and metabolism imbalance ( Rozenboim et al., 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…The improved FCR may be one of the reasons for the promoted growth in groups fed on probiotic diets. In this regard, several studies demonstrated an improvement in the growth and nutrient utilization by the addition of probiotics under the optimal or suboptimal nutritional levels ( Torres-Rodriguez et al., 2005 ; Kim et al., 2011 ; Salim et al., 2013 ; Bozkurt et al., 2014 ; Ravangard et al., 2017 ). The observed decrease in FCR may be associated with the improved intestinal status owing to modulating the intestine structure, secretion, microflora, or probiotics' anti-inflammatory impacts ( Fuller, 2001 ; Lutful Kabir, 2009 ; Olnood et al., 2015 ; Yadav and Jha, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, SCFAs have been shown to influence growth performance in broilers. Butyrate, in particular, is regarded as an available energy source, increasing the energy available to the host for growth (Ravangard et al 2017). Supplementing broiler diets with xylanase or XOS has been shown to affect the production of SCFA in the caeca of broiler chickens (Engberg et al 2004;Lee et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…in the caecum of broiler because the amount and kind of amino acids determined growth of the bacteria although the diets had same protein level. Ravangard et al (2017) used step down protein in their research and stated that caecum bacterial counts, Lactobacillus and Escherichia coli counts, were significantly not influenced by different nutritional content but only affected by inclusion of feed additive. In line with this study, the difference in the composition of the caecum microbiota might be caused by the addition of feed additive between control and prebiotics treatments while diet composition source of feed between basal and commercial feed.…”
Section: Grouping Of Caecum Bacterial Compositionmentioning
confidence: 99%